Family and cultural influences on cervical cancer screening among immigrant Latinas in Miami-Dade County, USA. Issue 6 (2nd June 2016) - Madhivanan, Purnima; Valderrama, Diana; Krupp, Karl; Ibanez, Gladys
Abstract: Cervical cancer disproportionately affects minorities, immigrants and low-income women in the USA, with disparities greatest among Latino immigrants. We examined barriers and facilitators to cervical cancer screening practices among a group of immigrant Latino women in Florida, USA. Between January and May 2013, six focus group discussions, involving 35 participants, were conducted among Hispanic women in Miami to explore their knowledge, beliefs about cervical cancer and facilitators and barriers to cervical cancer screening using a theoretical framework. The data showed that family support, especially from female relatives, was an important facilitator of screening and treatment. Women, however, reported prioritising family health over their own, and some expressed fatalistic beliefs about cancer. Major obstacles to receiving a Pap smear included fear that it might result in removal of the uterus, discomfort about being seen by a male doctor and concern that testing might stigmatise them as being sexually promiscuous or having a sexually transmitted disease. Targeted education on cancer and prevention is critically needed in this population. Efforts should focus on women of all ages since younger women often turn to older female relatives for advice.